Bowel movement frequency and risks of major vascular and nonvascular diseases: a population-based cohort study among Chinese adults - Yang, L; Yu, C; Guo, Y; Bian, Z; Fan, M; Yang, L; Du, H; Chen, Y; Yan, S; Zang, Y; Chen, J; Chen, Z; et al. (BMJ Publishing Group, 2020)
Objective The application of bowel movement frequency (BMF) in primary care is limited by the lack of solid evidence about the associations of BMF with health outcomes apart from Parkinson’s disease and colorectal cancer. We examined the prospective associations of BMF with major vascular and non-vascular diseases outside the digestive system.